Pengaruh Modal Intelektual Dan Risiko Perbankan Terhadap Nilai Perusahaan Melalui Corporate Perform Pada Industri Perbankan Di Bursa Efek Indonesia - Muhammad Faisal AR Pelu (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX - Sulawesi, 2019)
This study aims to know and analyze and influence of intellectual capital on corporate performance, analyze the influence of intellectual capital through corporate performance to company value, analyze the influence of intellectual capital to company value, analyze the influence of banking risk through corporate, analyze the influence of banking risk through corporate performance to company value, analyze the influence of banking risk to company value, and analyze influence of corporate performance the value of company. This research is in the form of explonatory research, used data by pooling. This research was conducted on banking sector companies in Indonesia. Observation were made for 4 consecutive years ie : 2012-2016. Method of analysis data used model of structural equation modeling (SEM). Result of this study shown: 1) Intelectual capital has positive and significant effent to corporate performance, 2) Intelectual capital has no significant effect on firm value through corporate performance, 3) Intellectual capital has positive and significant effent to company value, 4) Banking risk positive and significant impact on corporate performance 5), banking risk has a positive and significant impact on corporate value through corporate performance, 6). Banking risk has a positive and significant impact on corporate value, 7) Corporate performance has a positive and significant impact on firm value